First record of Hermatobatidae from China, with description of Hermatobates lingyangjiaoensis sp. n. (Hemiptera: Heteroptera) - Luo, Jiuyang; Chen, Pingping; Wang, Yanhui; Xie, Qiang (Zootaxa, 2019)
The family Hermatobatidae Poisson, 1965 is recorded for the first time from China and Hermatobates lingyangjiaoensis sp. n. is described. Photographs of the male and female habitus, legs, metasternum, and male genitalic structures, and scanning electron micrographs of the male metasternum and propleuron are provided. A key to all the species currently recognized in the H. weddi species group is presented. Distribution maps for the species of Hermatobates in China and Southeast Asia are also provided. Further, a photograph documenting the feeding of Hermatobates on Halovelia is presented for the first time to serve as direct evidence of the feeding habits of Hermatobates.